1982
DOI: 10.1080/17450398209425652
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the amino acid secretion and absorption in the stomach of the growing pig

Abstract: Two pigs of 35 kg live weight were fitted with re-entrant duodenal cannulas anterior to the pancreatic duct and fed barley-soya or casein-wheat starch diets prior to the experiment. After 24 hours fasting they were given a single meal of 15N-labelled free amino acids-wheat starch (A) or 15N-labelled wheat (B) diets and digesta leaving the stomach was collected during 12 hours. The proportion of TCA soluble N in total N of digesta increased with time from 10 to 40% with diet B and decreased from 90 to 47% with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Despite the pigs being fed different proteins and different ways of labelling with 15 N being used, the experimental data obtained supports the results of our previous study Zebrowska et al, 1992) and are in agreement with other experiments; Zebrowska et al (1982) and Souffrant et al (1986) indicating its validity for growing pigs. In the present experiment, N retention, related to intake, was 10% lower in comparison to the soyabean meal diet of the previous experiment (Zebrowska et al, 1992) due to lower apparent digestibility and higher urinary N excretion.…”
Section: Discussionsupporting
confidence: 81%
“…Despite the pigs being fed different proteins and different ways of labelling with 15 N being used, the experimental data obtained supports the results of our previous study Zebrowska et al, 1992) and are in agreement with other experiments; Zebrowska et al (1982) and Souffrant et al (1986) indicating its validity for growing pigs. In the present experiment, N retention, related to intake, was 10% lower in comparison to the soyabean meal diet of the previous experiment (Zebrowska et al, 1992) due to lower apparent digestibility and higher urinary N excretion.…”
Section: Discussionsupporting
confidence: 81%
“…This may be due both to the greater endogenous N secretion in the pigs given soya-bean protein and to the lower absorption of exogenous and endogenous N before the terminal ileum. The digestibility of endogenous N is less than the dietary N (Buraczewska et al 1975;Zebrowska et al 1976); while Zebrowska (1973) has shown that amounts of endogenous N of pigs given SBM, particularly in the proximal small intestine, were twice that obtained from pigs given other protein sources.…”
Section: Discussionmentioning
confidence: 99%
“…The values of the present experiment may be explained by the younger age of the pigs and by the frequency of feeding. The pigs in Expt 4 were fed every 2 h while those of Holmes et al (1974) and Zebrowska et al (1975) were fed twice daily. This frequent feeding may stimulate greater digestive secretions as Corring et al (1972) showed that there was an increase in protein secretion by the pig's pancreatic secretions in response to feeding.…”
Section: Discussionmentioning
confidence: 99%
“…The total amount of nitrogenous material entering the gut lumen is influenced by various dietary factors. It has been known for many years, for example, that the gut enzymatic secretions are influenced by both the amount and type of protein ( 9 , 10 ) . Plant non starch polysaccharides and potentially, resistant starch can greatly influence the loss of endogenous protein at the end of the ileum ( 11 , 12 ) .…”
Section: Sites and Sources Of Endogenous Proteinmentioning
confidence: 99%